Putting a Price on Carbon in South Africa and Other Developing Countries. - Winkler, Harald (Climate Policy Series., 2010)
How should we be putting a price on carbon, particularly in developing countries? This volume takes up this contested issue and examines how different economic instruments might apply in developing countries, with a special focus on South Africa. The papers included address a variety of themes in this area: Emissions trading, carbon taxes, fiscal and non-fiscal instruments, policy and institutional dimensions, and lessons from the Clean Development Mechanism. Presenting the very latest research, the volume will be of interest to academics and policymakers in economics, policy and development.